Pengembangan modul konseling krisis berfokus solusi untuk mereduksi kondisi trauma - Arri Handayani; Siti Fitriana; Senowarsito Senowarsito (Jurnal Konseling dan Pendidikan, 2022)
Crisis counseling promotion during the pandemic is important for the community since the crisis problems of an individual must receive immediate management. Thus, the problems must receive a solution-focused crisis counseling approach. This approach is deemed appropriate because the counseling is brief and could develop the potential of the counselee and also the problem solutions. This research aimed to 1) arrange the solution-focused crisis counseling module to reduce the children's trauma after the COVID-19 pandemic, 2) validate the module construction both from the content and appearance, and 3) revise the module based on expert judgment.This Research & Development took the research subjects during the preliminary analysis of need. The subjects were the guidance and counseling students that would join the child and adolescent counseling course.  On the other hand, the research subjects to validate the module consisted of experts in counseling and media.  The applied instruments were interviews and questionnaires.  The module validation involved experts in module materials and appearance. The applied data analyses were quantitative and qualitative descriptive data analyses.  The preliminary research results found that the students had no background knowledge of solution-focused crisis counseling although they needed the knowledge as a reference to promote counseling. The quantitative analyses of the counseling experts showed a total score between 56 to 68, categorized as excellent. On the other hand, the quantitative analysis results of the module-appearance expert obtained a score of 45, categorized as fairly excellent. The qualitative results showed that the module was reliable with some required revisions. After revising, the module could proceed to the subsequent processes, the research-subject group test